Adsorption of Water on Activated Carbon — a Thermodynamic Study by Immersion Calorimetry - M. Friedrich; K.H. Radeke; A.A. Isirikyan; R.S. Vartapetyan (Adsorption Science & Technology)
Heats of immersion of an industrial coke-based activated carbon into water have been measured as a function of water pre-adsorption. Using adsorption isotherm data, standard differential molar enthalpies and entropies of adsorption have been calculated. They illustrate the different molecular structures of the adsorbed water phase within the activated carbon. The two processes occurring, i.e. saturation of primary adsorption sites followed by subsequent filling of the total micropore volume, are clearly reflected by the thermodynamic data.